2019
DOI: 10.1111/acem.13666
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Computed Tomography Use for Pediatric Closed Head Injury Evaluation at a Nonpediatric Community Emergency Department

Abstract: Objective: The purpose of this study was to determine if implementation of a Pediatric Emergency Care AppliedResearch Network (PECARN)-based Closed Head Injury Assessment Tool could safely decrease computed tomography (CT) use for pediatric head injury evaluation at a nonpediatric community emergency department (ED).Methods: A quality improvement project was initiated at a nonpediatric community ED to implement an institution-specific, PECARN-based Pediatric Closed Head Injury Assessment Tool. Baseline head CT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 21 publications
0
19
1
Order By: Relevance
“…Both had either general paediatricians in the hospital34 or PEM physicians in the ED,35 allowing inhouse or direct clinical support, and were affiliated with an academic children’s hospital, a resource lacking in smaller community hospitals across the country. A third study, by Puffenbarger et al 36 showed a decrease in HCT rate of 20.8% in a community ED (preintervention HCT rate of 37.7% and postintervention HCT rate of 16.9%). Similar to our community ED, there was no inhouse paediatric support.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Both had either general paediatricians in the hospital34 or PEM physicians in the ED,35 allowing inhouse or direct clinical support, and were affiliated with an academic children’s hospital, a resource lacking in smaller community hospitals across the country. A third study, by Puffenbarger et al 36 showed a decrease in HCT rate of 20.8% in a community ED (preintervention HCT rate of 37.7% and postintervention HCT rate of 16.9%). Similar to our community ED, there was no inhouse paediatric support.…”
Section: Discussionmentioning
confidence: 95%
“…Three studies have engaged community EDs using QI and successfully reduced HCT rates 34–36. Two of the studies34 35 provided Maintenance of Certification for participating physicians.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13,15 This finding is particularly concerning as community hospitals provide the majority of pediatric emergency care. 1618…”
Section: Introductionmentioning
confidence: 99%
“…Intermediate‐risk MHI patients pose a challenge, because the rules recommend either CT or ED observation (based on clinical presentation and provider/parental preference). Implementation of PECARN rules in combination with clinical decision support systems and provider feedback has successfully reduced CT rates for all‐risk MHI patients in both pediatric and community EDs 7–9,11,12 . Moving forward, the intermediate‐risk MHI patients provide a challenging opportunity for improvement because CT scan utilization in this group remains high.…”
mentioning
confidence: 99%